Post-disaster Act of Merapi Community to Keep Water Catchment Area - Napsiah, Napsiah (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The spring coming from Mount Merapi is the main source of life for local residents, protecting the environment of Merapi is the main actions performed by the residents who live in the area. This study aims to know what Merapi community action to protect the environment. Data were collected by interviewing selected informants using the purposed sampling method who involved and knew the research topic and issues. There were three groups of informants who have subsequently interviewed by snowball sampling method. Non-participant observation was also conducted to triangulate data obtained from interview. The secondary data (through docementary analysis) was used to strengthen the primary data (intervew and observation). The results showed that the action based on local value dialoque and mutual agreement in fact couldnâ€™t stop exessive sand mining and exploitation on the slope of Merapi Mountain, it damaged water catchment area. The colective social action called â€œBela Lereng Merapiâ€ then done to stop the exessive mining, they overcamesucessfully.